2002
DOI: 10.2739/kurumemedj.49.35
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Secondary Spontaneous Pneumothorax Complicating Silicosis and Progressive Massive Fibrosis.

Abstract: Summary: To clarify the management and treatment for the refractory cases of secondary spontaneous pneumothorax (SSP), we analyzed the clinical features in SSP complicating three cases of advanced silicosis, and discussed the available treatment. All three cases were males of age ranging from 60 to 70 years, and had silicosis with massive progressive fibrosis (PMF), classified as type 4 (PR4) according to the ILO guidelines. There was no correlation between the onset of SSP and the smoking habit, or the durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…[24] Our findings support this hypothesis as shown in Table 1. According to an investigation by Bahrami and Mahjub in the stone-grinding factories where the study subjects had been employed, the concentration of silica compounds in the ambient air had been 25-50% higher than Occupational Safety and Health Administration (OSHA) levels.…”
Section: Discussionsupporting
confidence: 89%
“…[24] Our findings support this hypothesis as shown in Table 1. According to an investigation by Bahrami and Mahjub in the stone-grinding factories where the study subjects had been employed, the concentration of silica compounds in the ambient air had been 25-50% higher than Occupational Safety and Health Administration (OSHA) levels.…”
Section: Discussionsupporting
confidence: 89%
“…OK432, a sclerosing agent used only in certain parts of Asia, has been used for the treatment of malignant pleural effusion, 16,23 , 24 pneumothorax 27 and chylothorax 28 . Although the efficacy of monotherapy with OK432 for pleurodesis of malignant pleural effusion has been evaluated, 16 this study showed that the efficacy was further improved when it was used in combination with cisplatin.…”
Section: Discussionmentioning
confidence: 93%
“…In a case series study, Kawano et al suggested that there was no correlation between the onset of SSP and duration of occupational exposure to silica [ 24 ]. Our findings support this hypothesis as shown in Table 1 .…”
Section: Discussionmentioning
confidence: 99%